Communicative Of Future Educators Innovation in the Formation of Competence Psychological and Pedagogical Possibilities of the Approach (Eurasian Journal of Learning and Academic Teaching, 2022)
The article deals with the psycho-pedagogical aspects of innovative approaches to the formation of communicative competence of future teachers